Factors Related to Health–Promoting Behaviors Among Andropause in Community - ฟักแก้ว จุฬาลักษณ์; บุญเชียง วราภรณ์; จันทโสภีพันธ์ พนิดา (Nursing Journal CMU, 2019)
Andropause is a part of the male human life cycle. Men experiencing andropause may have degeneration of health. Men with andropause are found to have health problems and inappropriate health behaviors. Therefore, knowing the factors that are related with these behaviors will help men develop more appropriate health behaviors. This descriptive correlational study aimed to investigate health promoting behaviors and the factors related to them among men with andropause. The participants consisted of 110 men recruited by purposive sampling with andropause aged between 40 to 59 years old who live in Saraphi, Chiang Mai. The data were collected in July 2017. The instruments used in this study were questionnaires developed by the researcher based on literature review. The conceptual framework used for this study came from Pender’s Health Promotion Model. All questionnaire parts had content validity indices of .96 and reliability values between .71 and .86. Data were analyzed using descriptive statistics and Spearman rank correlation coefficient. The main results of this study revealed that, the participants had good levels of health promoting behaviors (x ̅= 94.85, S.D. = 10.98); the score for food consumption behaviors was at the highest level (= 25.75, S.D.= 3.69). The score for exercise behaviors was at the lowest level (= 15.22, S.D.= 3.45). The perceived benefits, the perceived self–efficacy, the activity-related effect, the interpersonal influences and the situational influences had statistically positive relationships, and health promoting behaviors were statistically significant (r = .324, p< .001, r = .620, p< .001, r = .674, p< .001, r = .580, p< .001, r = .591, p< .001). Perceived barriers had a statistically negative relationship to health promoting behaviors and was statistically significant (r = -.429, p< .001). These research findings could be used as basic information for public health agencies to promote appropriate health-promoting behaviors among men with andropause.